AB0624 SAFETY OF RITUXIMAB BIOSIMILAR FOR THE TREATMENT OF CRYOGLOBULINEMIC VASCULITIS. (June 2019) - Vacchi, Caterina; Visentini, Marcella; Cicco, Maria DI; Angelotti, Francesca; Lauletta, Gianfranco; Manfredi, Andreina; Filippini, Davide; Tavoni, Antonio; Casato, Milvia; Castelnovo, Laura; Monti, Giuseppe; Pietrogrande, Maurizio; et al.
Abstract : Background: Rituximab (RTX) represents a milestone in the treatment of mixed cryoglobulinemic vasculitis (MCV). Despite usually well-tolerated, RTX may induce different types of adverse drug reactions, including exacerbation of vasculitis. RTX biosimilars have been recently approved in Europe in the treatment of rheumatoid arthritis, but no data are available about effectiveness and safety of RTX biosimilars in the treatment of MCV. Objectives: Aim of the study was to analyse the safety of RTX biosimilar in patients with MCV treated in first-line or after a shift by RTX originator. Methods: In a multicenter, prospective, open-label study, we enrolled all MCV patients treated with RTX biosimilar, both in first-line or after a shift by RTX originator. Nineteen consecutive MCV patients (F/M 13/6, mean age 68.3±11.5 months, mean disease duration 94±86 months, 10/19 HCV+ and 6/19 HBV+) were treated with RTX in a six-month period (July-December, 2018). Nine patients were treated with RTX for the first time, while the other 9 patients have been already treated with RTX originator and were switched to RTX biosimilar. Twelve patients received a dose of 250 mg/m 2 of RTX every other week, while 6 were treated with 1 gram of RTX every other week. Results: During a month-period after the last infusion, 5 adverse events (AE) were observed, namely 2 vasculitis flares, and 1 urticaria, atrial fibrillation occurred during infusion, and septicaemia, respectively. Three of 5 aE were observed in patients treated with the higher dose of RTX (in particular both cases of vasculitis flare were recorded in patients treated with 1 gram of RTX), while no differences were observed according to the previous treatment with RTX originator (2/9 vs 3/9 aE in patients switch or naïve, respectively). Conclusion: Despite the low number of patients, the switch among RTX originator and biosimilar appear to be safe and the number of aE were in line with previous reports about RTX originator. The main limit of this study is the absence of a control group, that doesn't allow a direct comparison of the safety between RTX originator and biosimilar. Previous reports suggested that higher dosage of RTX are associated to a higher risk of side effects. Also, in our study the occurrence of aE, mainly vasculitis flare, seem to be associated to the dose of RTX, rather than to the switch to biosimilar References: [1] Ferri C, Cacoub P, Mazzaro C, Roccatello D, Scaini P, Sebastiani M, Tavoni a, Zignego aL, De Vita S. Treatment with rituximab in patients with mixed cryoglobulinemia syndrome: results of multicenter cohort study and review of the literature. Autoimmun Rev. 2011;11:48-55 [2] Sène D, Ghillani-Dalbin P, amoura Z, Musset L, Cacoub P. Rituximab may form a complex with IgMkappa mixed cryoglobulin and induce severe systemic reactions in patients with hepatitis C virus-induced vasculitis. Arthritis Rheum. 2009;60:3848-55. Disclosure of interests: None declared